E-Voting as a Panacea to Voter Apathy in Nigeria - Oyoru, Rashida Adamu; Birisan, Lawal Yusuf; Towoju, Adedoyin John; Otohinoyi, Samuel (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025, 2025)
Voter apathy has emerged as one of the most critical challenges to democratic consolidation in Nigeria. Despite the adoption of reforms intended to strengthen electoral credibility, turnout has consistently declined, raising concerns about the legitimacy of governance. This paper examines the potential of electronic voting (e-voting) as a panacea to voter apathy in Nigeria. Anchored on Rational Choice Theory, the study argues that citizens often disengage when the costs of participation outweigh the benefits. Drawing on secondary sources, comparative experiences from countries such as Estonia and Brazil, and institutional reports from Nigeria, the study finds that e-voting can reduce apathy by improving transparency, minimizing electoral violence, and enhancing inclusivity. However, infrastructural deficits, cybersecurity concerns, and institutional weaknesses remain obstacles to its adoption. The paper concludes that while e-voting offers a pathway to revitalizing participation, it must be embedded within broader electoral reforms to strengthen institutions, build citizen trust, and promote inclusivity.